Preliminary analyses on decontamination factors during pool scrubbing with bubble size distributions obtained from EPRI experiments - Yoonhee Lee; Yong Jin Cho; Inchul Ryu (Nuclear Engineering and Technology, 2021)
In this paper, from a review of the size distribution of the bubbles during pool scrubbing obtained from experiments by EPRI, we apply the bubble size distributions to analyses on the decontamination factors of pool scrubbing via I-COSTA (In-Containment Source Term Analysis). We perform sensitivity studies of the bubble size on the various mechanisms of deposition of aerosol particles in pool scrubbing. We also perform sensitivity studies on the size distributions of the bubbles depending on the diameters at the nozzle exit, the molecular weights of non-condensable gases in the carrier gases, and the steam fractions of the carrier gases. We then perform analyses of LACE-ESPAÑA experiments and compare the numerical results to those from SPARC-90 and experimental results in order to show the effect of the bubble size distributions.